Association of Social Determinants of Health With Rapid Response Events: A Retrospective Cohort Trial in a Large Pediatric Academic Hospital System - Lawson, Nikki R.; Acorda, Darlene; Guffey, Danielle; Bracken, Julie; Bavare, Aarti; Checchia, Paul; Afonso, Natasha S. (Frontiers in Pediatrics, 2022)
Background Social determinants of health (SDH) are known to impact hospital and intensive care unit (ICU) outcomes. Little is known about the association between SDH and pediatric rapid response (RR) events and understanding this impact will help guide future interventions aimed to eliminate health disparities in the inpatient setting. Objectives The primary objective of this study is to describe the association between SDH and RR utilization (number of RR events, time to RR event, shift of event and caller). The secondary objective is to determine if SDH can predict hospital length of stay (LOS), ICU transfer, critical deterioration (CD), and mortality. Methods A retrospective cohort study was conducted. We reviewed all RR events from 2016 to 2019 at a large, academic, pediatric hospital system including a level 1 trauma center and two satellite community campuses. All hospitalized patients up to age 25 who had a RR event during their index hospitalization were included. Exposure variables included age, gender, race/ethnicity, language, income, insurance status, chronic disease status, and repeat RR event. The primary outcome variables were hospital LOS, ICU transfer, CD, and mortality. The odds of mortality, CD events and ICU transfer were assessed using unadjusted and multivariable logistic regression. Associations with hospital LOS were assessed with unadjusted and multivariable quantile regression. Results Four thousand five hundred and sixty-eight RR events occurred from 3,690 unique admissions and 3301 unique patients, and the cohort was reduced to the index admission. The cohort was largely representative of the population served by the hospital system and varied according to race and ethnicity. There was no variation by race/ethnicity in the number of RR events or the shift in which RR events occurred. Attending physicians initiated RR calls more for event for non-Hispanic patients of mixed or other race (31.6% of events), and fellows and residents were more likely to be the callers for Hispanic patients (29.7% of events, p = 0.002). Families who are non-English speaking are also less likely to activate the RR system (12% of total RR events, p = 0.048). LOS was longest for patients speaking languages other than Spanish or English and CD was more common in patients with government insurance. In adjusted logistic regression, Hispanic patients had 2.5 times the odds of mortality (95% CI: 1.43–4.53, p = 0.002) compared with non-Hispanic white patients. Conclusion Disparities exist in access to and within the inpatient management of pediatric patients. Our results suggest that interventions to address disparities should focus on Hispanic patients and non-English speaking patients to improve inpatient health equity. More research is needed to understand and address the mortality outcomes in Hispanic children compared to other groups.